The Venetian Money Market Banks, Panics, and the Public Debt, 1200-1500 - Mueller, Reinhold C. (Johns Hopkins University Press, 2019)
The long awaited conclusion to the magisterial Money and Banking in Medieval and Renaissance Venice.Originally published in 1997. In 1985 Frederic C. Lane and Reinhold C. Mueller published the magisterial Money and Banking in Medieval and Renaissance Venice, volume 1: Coins and Moneys of Account. Now, after ten years of further research and writing, Reinhold Mueller completes the work that he and the late Frederic Lane began. The history of money and banking in Venice is crucial to an understanding of European economic history. Because of its strategic location between East and West, Venice rapidly rose to a position of preeminence in Mediterranean trade. To keep trade moving from London to Constantinople and beyond, Venetian merchants and bankers created specialized financial institutions to serve private entrepreneurs and public administrators: deposit banks, foreign exchange banks, a grain office, and a bureau of the public debt. This new book clarifies Venice's pivotal role in Italian and international banking and finance. It also sets banking-and panics-in the context of more generalized and recurrent crises involving territorial wars, competition for markets, and debates over interest rates and the question of usury.